Tumor suppressive miR-6775-3p inhibits ESCC progression through forming a positive feedback loop with p53 via MAGE-A family proteins. Issue 11 (November 2018) - Meng, Lingjiao; Liu, Fei; Ju, Yingchao; Ding, Pingan; Liu, Sihua; Chang, Sheng; Liu, Shina; Zhang, Yi; Lian, Yishui; Gu, Lina; Zhang, Xiaochong; Sang, Meixiang
Abstract Accumulating evidences indicate that microRNAs (miRNAs) play vital roles in multiple diseases, including cancer. In the present study, we showed that miR-6775-3p plays a tumor suppressive role in esophageal squamous cell carcinoma (ESCC). High expression miR-6775-3p is associated with good clinical outcomes of ESCC patients. Over-expression of miR-6775-3p inhibited tumor growth and liver metastasis of ESCC xenograft tumors. Enforced expression of miR-6775-3p inhibited ESCC cell proliferation, migration, and invasion. KEGG pathway analysis revealed that miR-6775-3p was associated with the genes on "pathway in cancer". Mechanically, miR-6775-3p inhibited the expression of tumor antigens MAGE-A family through direct binding the 3′UTR region of MAGE-A mRNAs, and attenuated MAGE-A-inhibited transcriptional activity of tumor suppressor p53. In addition, miR-6775-3p also directly inhibits its host gene SLC7A5 which has been reported to play oncogenic roles in cancer progression. Interestingly, miR-6775-3p and its host gene SLC7A5 were directly transcriptionally induced by p53. Thus, for the first time, our study proposed a novel positive feedback regulation between miR-6775-3p and p53 via MAGE-A family, which plays crucial role in ESCC progression.